(untitled) (Research, Society and Development, 2022)
The quality of the fine wine produced is related to the grape used and also to the technologies used in the process. The oenological inputs that are used in the elaboration guarantee the wine a differential in front of consumers. In this context, the objective of the present work was to carry out a survey of the costs of production inputs for the elaboration of fine, red and white wines, and the use of linear optimization to maximize production profit. Data were collected on the amounts of inputs used in three fine wines, two red Cabernet Sauvignon, Malbec and one white Muscat Petit Grain, produced in the Lower Middle of the São Francisco Valley. For this, a Linear Optimization model was elaborated with three scenarios, in the first one the real data of the elaboration of the three wines was used, in the second there was the restriction of bottles and corks and in the third the restriction of a single input. The results of the mathematical programming made it possible to predict the required amount of liters of each type of wine to be made to maximize profit according to each scenario presented.